A novel thermal sensor concept for flow direction and flow velocity - Nguyen, Nam-Trung (2012)
This paper presents a unified theory for different measurement concepts of a thermal flow sensor. Based on this theory, a new flow sensor concept is derived. The concept allows measuring both direction and velocity of a fluid flow with a heater and an array of temperature sensors. This paper first analyzes the two-dimensional (2-D) forced convection problem with a laminar flow. The two operation modes of a constant heating power and of a constant heater temperature are considered in the analytical model. A novel estimation algorithm was derived for the flow direction. Different methods for velocity measurement were presented: the hot-wire method, the calorimetric method, and the novel average-temperature method. The only geometric parameter of the sensor, the dimensionless position of the sensor array, is optimized based on the analytical results. Furthermore, the paper presents the experimental results of the sensor prototype. In order to verify the analytical model, an array of temperature sensors was used for recording the 2-D temperature profile around the heater. Temperature values are transferred to a computer by a multiplexer. A program running on a personal computer extracts the actual flow velocity and flow direction from the measured temperature data. This paper discusses different evaluation algorithms, which can be used for this sensor. A simple Gaussian estimator was derived for the direction measurement. This estimator provides the same accuracy as the analytical estimator. Velocity results of both the calorimetric concept and the novel average-temperature concept are also presented.